2010
DOI: 10.1039/b917759k
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic technology for biomolecule applications: a critical review

Abstract: In this review, we present nanofluidic phenomena, particularly as they relate to applications involving analysis of biomolecules within nanofabricated devices. The relevant length scales and physical phenomena that govern biomolecule transport and manipulation within nanofabricated nanofluidic devices are reviewed, the advantages of nanofabricated devices are presented, and relevant applications are cited. Characteristic length scales include the Debye length, the Van der Waals radius, the action distance of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
135
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(136 citation statements)
references
References 178 publications
(215 reference statements)
0
135
0
1
Order By: Relevance
“…As NVNs are, in essence, combinations of nanofluidic devices 45 and microreactors 46 , solid-state microfluidic and nanofluidic devices accommodate some of their functions and properties [47][48][49] . Cell blebbing 50 is an alternative method by which to obtain unilamellar .…”
Section: Previous Techniques and Alternative Methodsmentioning
confidence: 99%
“…As NVNs are, in essence, combinations of nanofluidic devices 45 and microreactors 46 , solid-state microfluidic and nanofluidic devices accommodate some of their functions and properties [47][48][49] . Cell blebbing 50 is an alternative method by which to obtain unilamellar .…”
Section: Previous Techniques and Alternative Methodsmentioning
confidence: 99%
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 New effects have been revealed in nanoscale fluidic channels such as physical confinement of macromolecules (e.g., nucleic acids) 3,4 and unique ionic transport mechanisms, [5][6][7] which fuel numerous innovative studies. In particular, the static and dynamic properties of single DNA molecule confined in nanochannels ranging from tens to hundreds of nanometers have been well characterized, 8 and applications including DNA stretching 9,10 and DNA entropic trapping 11 have been reported.…”
Section: Introductionmentioning
confidence: 99%